2014
DOI: 10.1021/nn500100x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Intracellular Delivery of Molecules with High Cell Viability Using Nanosecond-Pulsed Laser-Activated Carbon Nanoparticles

Abstract: Conventional physical and chemical methods that efficiently deliver molecules into cells are often associated with low cell viability. In this study, we evaluated the cellular effects of carbon nanoparticles believed to emit photoacoustic waves due to nanosecond-pulse laser activation to test the hypothesis that this method could achieve efficient intracellular delivery while maintaining high cell viability. Suspensions of DU145 human prostate carcinoma cells, carbon black (CB) nanoparticles, and calcein were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…Carbon black (CB) NP-sensitized photoporation was first reported by the group of Prausnitz [77,78]. They reported that thermal effects are not the main reason for membrane poration.…”
Section: Carbon Nanostructure-sensitized Photoporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon black (CB) NP-sensitized photoporation was first reported by the group of Prausnitz [77,78]. They reported that thermal effects are not the main reason for membrane poration.…”
Section: Carbon Nanostructure-sensitized Photoporationmentioning
confidence: 99%
“…In a comparative study of thermal vs. VNB mediated membrane poration, it has been found that VNB-mediated membrane poration actually allows more efficient uptake of exogenous nanomaterials with reduced cytotoxicity as compared to thermal poration at low laser intensity [76]. Although AuNPs are the most widely used for membrane poration, other nanomaterials like titanium nanostructures and carbon-based nanomaterials are also currently being evaluated as alternative sensitizing NPs [77][78][79][80].…”
Section: Introductionmentioning
confidence: 99%
“…In this method, we expose CB nanoparticles to nanosecond pulsed laser, causing the nanoparticles to preferentially heat up, which results in particle expansion [27], liquid vaporization [27,28] and/or chemical reaction (C[s] + H 2 O[l] → CO[g] + H 2 [g]) [29], followed by generation of acoustic waves, leading to poration of cell membranes [30,31]. Molecules then passively transport into the cell without the need of endocytosis.…”
mentioning
confidence: 99%
“…Molecules then passively transport into the cell without the need of endocytosis. Previously we demonstrated this method to be efficient in delivering small molecules like calcein and larger proteins like bovine serum albumin [30,31]; here we seek to extend the application to siRNA not only to show intracellular uptake of siRNA, but to demonstrate RNA interference by knocking down expression of a specific gene by delivery of biologically active siRNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation